2009
DOI: 10.1088/0964-1726/18/10/104015
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional electro-fluid–structural interaction simulation for pumping performance evaluation of a valveless micropump

Abstract: In this study, the pumping performance of a piezoelectric valveless micropump is simulated. The micropump, which was developed in the previous work, is composed of a four-layer lightweight piezocomposite actuator, a polydimethylsiloxane (PDMS) pump chamber, and two diffusers. The piezoelectric domain, the fluid domain and the structural domain are coupled in the three-dimensional simulation. We used ANSYS for the piezoelectric and structural domains and ANSYS CFX for the fluid domain. The effects of driven fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…They reported an increased numerical complexity of the model at higher actuating frequencies. Similar models (on diffuser type micropumps) were reported also in references [1113]; the simulation results of the last two references show good agreement with measurements on fabricated devices. An alternative to numerical modeling is to design microfluidic devices using electric circuit analogy, as recently reviewed by Oh et al [14].…”
Section: Introductionsupporting
confidence: 84%
“…They reported an increased numerical complexity of the model at higher actuating frequencies. Similar models (on diffuser type micropumps) were reported also in references [1113]; the simulation results of the last two references show good agreement with measurements on fabricated devices. An alternative to numerical modeling is to design microfluidic devices using electric circuit analogy, as recently reviewed by Oh et al [14].…”
Section: Introductionsupporting
confidence: 84%
“…Application of this multidimensional technique to study the flow in valveless micropumps has been realized by Tsui and Lu and Ha et al . . It was shown that reasonably good agreement was obtained in comparison with experiments.…”
Section: Introductionsupporting
confidence: 56%
“…Sayar et al [28] carried out a detailed study of a micropump using CFD studies. Ha et al [29] and Yao et al [30] carried out 3-D electro-fluidsolid analysis of valveless micropumps using CFD tools. Cui et al [31] presented a micropump that integrates with microneedles and microsensor as part of a controlled drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many approximate analytical and simulation models have been reported [22][23][24][25][26][27][28][29][30][31][32][33]. However, in spite of considerable work in the area of valveless micropump, investigations of combined electro-fluid-structural interactions are limited due to the complicated physics involved.…”
Section: Introductionmentioning
confidence: 99%